Hubungan Kecerdasan Emosi dan Penyesuaian Diri pada Dewasa Awal yang Menikah - Tasya Gita Fitri; Fatin Rohmah Nur Wahidah; Dyah Astorini Wulandari; Herdian Herdian (PSIMPHONI, 2024)
Marriage is a union between two individuals who rely on each other, provide mutual support, and build a shared life. Self-adjustment and emotional intelligence are essential factors in fostering marital harmony. Married couples with a high level of self-adjustment and emotional intelligence tend to evaluate various situations in their marital life more positively. This study employs a descriptive correlational method with 170 respondents selected through accidental sampling. The instruments used include the Emotional Intelligence Scale and the Self-Adjustment Scale. Data analysis was conducted using the Pearson Product-Moment Correlation technique. The results indicate a positive and significant relationship between emotional intelligence and self-adjustment in married individuals in early adulthood (r = 0.262, p = 0.001; p < 0.05). Based on these findings, it is recommended that married couples enhance their emotional intelligence through emotional management training and communication skills development to improve self-adjustment in marriage. Additionally, psychological intervention programs focusing on strengthening adaptation skills in marital life can help couples navigate marital challenges more effectively.